The Development of Management System of Intellectual Work for Increasing Energy Efficiency of Companies - Deputatova, Ludmila Nikolaevna; Mukhina, Eugeniia Rinatovna; Marinina, Anna Valerevna; Postnikov, Vladimir Pavlovich; Lazukova, Eugeniia Andreevna (International Review of Management and Marketing, 2016)
In modern terms, interesting creative work in the close-knit team is becoming a major factor determining the choice of a good specialist. Provision of this factor in the enterprise becomes an important issue in the intellectual work management system. The activity of modern enterprises is connected with intellectual work. The features of intellectual work should be taken into account in the management and motivation of employees of industrial enterprises. The article presents the elements of the control system of intellectual work and their focus on the formation and maintenance of the company's values. Creating conditions for self-development and self-realization, the formation of team spirit, employee training system allows activate the human potential of the company. The article suggested the concept of intelligent control system as a set of interrelated forms of incentives and organizational and motivational mechanisms to facilitate activation of knowledge workers. Continuous improvement techniques and technologies defined structural changes in the labor management system of the organization workers. The authors developed and implemented a method of estimating intellectual work management efficiency in order to improve energy efficiency. It included the method of determining the level of efficiency and a method of imaging evaluation. The proposed method gives a possibility to establish ways to improve the management system in intellectual work for further improving energy efficiency. This article has experimental character. Keywords: energy efficiency; management system of intellectual work; motivation; evaluation method. JEL Classifications: O34, J53, Q40